Micro, Small and Medium Enterprises’ Understanding in Preparing Financial Statements Based on SAK ETAP - Mawardi, Wisnu; Woyanti, Nenik; Iriviana, Lala; Darwanto, Darwanto (International Journal of Economics and Financial Issues, 2019)
Micro, small and medium enterprises (MSMEs) sector in Indonesia plays an important role in developing the economic growth, but it still has some problems. One of the problems faced by MSMEs sector is the preparation of financial reports that are in accordance with the standards for preparing financial statements, namely SAK ETAP (Financial Accounting Standards for Entities without Public Accountability). MSMEs uses financial statement as a reference in efforts to develop MSMEs. The purpose of this study is to analyze and determine the influence of information and socialization, education levels, scale of business, and the company’s age on MSMEs’ understanding in preparing financial statements based on SAK ETAP. The sample of this study is owners of MSMEs in Semarang. The method of determining the sample uses a random sampling method (the research sample was 50 respondents). Data are analyzed using logistic regression analysis. The results show that the provision of information and socialization, business scale, and education level have a significant influence on the understanding of MSMEs in preparing financial statements based on SAK ETAP, while the company’s age does not affect the understanding of MSMEs in preparing financial statements based on SAK ETAP. Keywords: MSMEs, financial reports, SAK ETAP, logistic regression JEL Classifications: A1; C01; M41 DOI: https://doi.org/10.32479/ijefi.8748